Increasing Youth Creativity in Making Jewelry Based on Local Wisdom of the Archipelago: Peningkatan Kreativitas Remaja Karang Taruna dalam Membuat Perhiasan Berbasis Kearifan Lokal Nusantara - Ariani Ariani; Awang Eka Novia Rizali; Erlina Novianti; Resky Annisa Damayanti; Silviana Amanda Aurelia Tahalea; Mahsa Raffa Luthta; Naufal Ananta Nugraha; Raphael Jordan Ali; Siti Marshaula Lyravega (Universitas Muhammadiyah Palembang, 2025)
Youth of Karang Taruna in Kedoya Selatan Urban Village, Kebon Jeruk Sub-district, West Jakarta, have had several activities, but they have not been directed towards activities that stimulate their creativity. In addition to Karang Taruna's routine activities such as community service and daily activities such as school or college, they spend time accessing information in social media or playing games, which are more pleasure-based. The ease of accessing information from outside has an impact on their interest in foreign cultures (Korean, Japanese, American) which sometimes tends to be excessive. Referring to these conditions, the PkM (Community Service) team of FSRD (Faculty of Art and Design) decided to hold an activity aimed at increasing the creativity of Karang Taruna teenagers as well as providing knowledge about the rich culture of the archipelago. The PkM activity in the form of training in making jewelry based on the local wisdom of the archipelago was attended by 8 participants aged 18-20 years and applied the mentoring method with a PAR (Participatory Action Research) approach. The results of the activity are in the form of jewelry making skills and insight into the culture of the archipelago (Karo, Nias, Sumba) as a source of inspiration, implemented in the form of jewelry earrings, necklaces, rings, and brooches in the form of a spiral base. This activity is expected to be a productive activity for Karang Taruna while increasing their appreciation for the archipelago's culture.